(untitled) (Al-Academy, 2024)
the study aimed to find out the impact of teaching using Generative Artificial Intelligence tools (GAI) on enhancing digital design skills among multimedia students at the School of Arts and Design, the University of Jordan.The researcher followed the semi-experimental approach to the nature of the study, the students were deliberately selected and the people were randomly distributed. The study community is made up of 38 students from the School of Arts and Design at the University of Jordan for the third semester of 2020-2022.The sample was divided into two groups: an experimental group of 18 students who were taught using an educational application based on Artificial Intelligence (Midjourny), and and the others who was taught in the usual way.To achieve the objectives of the study, the researcher built an A digital design skills assessment tool (product evaluation card) was used in the Fundamentals of Design 2 course, and its validity and reliability were ensured.The results revealed statistically significant differences at a significance level of (α = 0.05) between the mean scores of the two groups in the dimensional performance of digital design skills, in favor of the experimental group that was taught using the Artificial Intelligence application (Midjourny).The study concluded with several recommendations, including adopting Artificial Intelligence applications as an educational strategy for students in the College of Arts and Design.